A multi-approaches examination of toxicological effects of a naturally-occurring plant alkaloid veratridine, and the synthetic type II pyrethroid lambda-cyhalothrin on honey bees - Aklesso Kadala; Mercédès Charreton; Michel Pélissier; Jérôme Mutterer; Mohamed Chahine; Pierre Charnet; Claude Collet (Environmental Toxicology and Pharmacology, 2026)

Unravelling impacts of the insecticide deltamethrin on neuronal sodium channels in honey bees: Molecular insights and behavioural outcomes - Aklesso Kadala; Mahira Kaabeche; Mercédès Charreton; Jérôme Mutterer; Michel Pélissier; Thierry Cens; Matthieu Rousset; Mohamed Chahine; Pierre Charnet; Claude Collet (Chemosphere, 2024)

Obesity of mice lacking VAP-1/SSAO by Aoc3 gene deletion is reproduced in mice expressing a mutated vascular adhesion protein-1 (VAP-1) devoid of amine oxidase activity - Valentin Jargaud; Sandy Bour; François Tercé; Xavier Collet; Philippe Valet; Anne Bouloumié; Jean-Claude Guillemot; Pascale Mauriège; Sirpa Jalkanen; Craig Stolen; Marko Salmi; David J. Smith; et al. (Journal of Physiology and Biochemistry, 2021)

Windstorm‐induced canopy openings accelerate temperate forest adaptation to global warming - Lucie Dietz; Catherine Collet; Jean‐Luc Dupouey; Eric Lacombe; Lisa Laurent; Jean‐Claude Gégout (Global Ecology and Biogeography, 2020)
Aim Climate change is known to be a driver of changes in forest plant communities and to modify disturbance regimes. We investigated whether forest gaps favoured vegetation adaptation to warmer climates by accelerating the shift of plant communities to a warmer‐adapted composition independently of canopy closure linked to natural forest dynamics. Location Temperate and mountainous forests of France. Time period 2002–2018. Major taxa studied Vascular plants. Methods Using floristic surveys conducted in 2002 and 2018 in 139 permanent plots set up in unmanaged forest gaps created by windstorms in 1999, we assessed the plant communities’ changes in context of global warming. We also compared gap communities to closed communities inventoried in undisturbed forest. A community temperature index (CTI) and a community light index (CLI) were computed for each floristic survey with species temperature optima and Ellenberg light indicator values, respectively. Results CTI increased significantly in the gaps over the 16 years by 0.11°C/decade on average. During the same period, the CLI decreased, indicating that community thermophilization was not the direct result of an increase in solar radiation linked to gap creation. Models showed that, after canopy recovery, thermophilization was stronger in mountains (+0.54°C) than lowland sites (+0.12°C) compared to undisturbed forests. The difference between former gaps and undisturbed forests resulted from the colonization of warm adapted species and the decline of cold adapted species in gaps. Main conclusions For a given canopy closure, our results show that thermophilization of understorey communities is higher in areas with previous disturbances than in undisturbed forests. By increasing the speed of thermophilization, the disturbance regime plays a key role in the adaptation of forest communities to climate warming. The effects of large‐scale disturbances on forest plant composition should therefore not be overlooked, especially since disturbance regime tends to intensify with climate change.

Neuroplasticity of imagined wrist actions after spinal cord injury: a pilot study - Franck Di Rienzo; Aymeric Guillot; Sébastien Mateo; Sébastien Daligault; Claude Delpuech; Gilles Rode; Christian Collet (Experimental Brain Research, 2015)

Characterization of the first honeybee Ca2+ channel subunit reveals two novel species- and splicing-specific modes of regulation of channel inactivation - Thierry Cens; Matthieu Rousset; Claude Collet; Valérie Raymond; Fabien Démares; Annabelle Quintavalle; Michel Bellis; Yves Le Conte; Mohamed Chahine; Pierre Charnet (Pflügers Archiv - European Journal of Physiology, 2013)

Stable tumor vessel normalization with pO2 increase and endothelial PTEN activation by inositol trispyrophosphate brings novel tumor treatment - Claudine Kieda; Bouchra El Hafny-Rahbi; Guillaume Collet; Nathalie Lamerant-Fayel; Catherine Grillon; Alan Guichard; Jozef Dulak; Alicja Jozkowicz; Jerzy Kotlinowski; Konstantina C. Fylaktakidou; Aurélien Vidal; Philippe Auzeloux; et al. (Journal of Molecular Medicine, 2013)

Excitation-contraction coupling in skeletal muscle fibers from adult domestic honeybee - Claude Collet (Pflügers Archiv - European Journal of Physiology, 2009)

Effects of extracellular ATP on freshly isolated mouse skeletal muscle cells during pre-natal and post-natal development - Claude Collet; Caroline Strube; László Csernoch; Nora Mallouk; Carlos Ojeda; Bruno Allard; Vincent Jacquemond (Pflügers Archiv - European Journal of Physiology, 2002)